Kajian Teknis Penerangan Jalan Umum Kawasan Industri dan Pergudangan di Jalan Margomulyo Surabaya - Dimas Katon Aji Dharma; Aris Heri Andriawan; Izzah Aula Wardah (Uranus: Jurnal Ilmiah Teknik Elektro, Sains dan Informatika, 2025)
Street lighting is infrastructure that the community needs at night, as a support for improving the safety, comfort and security of motorists. Street lighting sometimes still does not comply with the standards determined by the National Standards Body 7391:2008, so sometimes it requires recalculation according to the standard requirements determined by the National Standards Body. Jalan Margomulyo Surabaya is an arterial road with a width of 11 meters and a length of 4000 meters. This road is an industrial and warehouse area which is passed by large trucks of cars, motorbikes and the surrounding community every day. The lighting on Jalan Margomulyo is still found to be less than optimal and there are still black spots at several points, so re-planning needs to be done to produce maximum lighting. On Jalan Margomulyo there are around 90 ornamental poles with 120 Watt LED lights. Which produces an average illumination of 13.9 lux and consumes energy of 129.6 Kwh/day. However, the results of the lights installed in the field produced an average illumination that was less than optimal, so re-planning was carried out using 150 Watt LED lights with an ornamental handlebar angle of 19.19 for 90 light points along the road, which would produce an average illumination of 19.09 lux, light intensity 1863.05 cd which is in accordance with the National Standards 7391:2008.